Impact of Work Discipline on Productivity at PT. Win Textile Purwakarta - Indriyanti, Lia; Surachman, Tisna; Saifudin, Saifudin (Pascasarjana Universitas Pasundan, 2023)
Human resources are the main factor in running a company, so good management is needed to optimize employee performance in achieving company targets. One important aspect in human resource management is the implementation of work discipline, which plays a role in enforcing company regulations. This study was conducted in the Knitting Factory 1 department of PT Win Textile Purwakarta to analyze the effect of work discipline on productivity, considering the still high number of reject fabrics. This study involved 77 employees as respondents. The results of the analysis showed that work discipline had a significant effect on productivity of 20.4%, while 79.6% was influenced by other factors. The results of the significance test showed t count 4.381> t table 1.665 with sig 0.000 <0.05, so that work discipline was proven to have a positive and significant effect on employee productivity.